THE ROLE OF BRAND AWARENESS IN MEDIATING THE INFLUENCE OF KEY OPINION LEADERS (KOL) ON PURCHASE INTENTION FOR MUSTIKA RATU FACE MASK PRODUCTS (A STUDY ON TIKTOK USERS IN DENPASAR CITY) - Ni Made Viviani Saraswaty; Tjokorda Gde Raka Sukawati (Adisam Publisher, 2025)
This study aims to examine the role of brand awareness in mediating the influence of key opinion leaders (KOL) on purchasing intention in Mustika Ratu face mask products, focusing on TikTok users in Denpasar City. The number of respondents in this study was 107 people, who were selected using a non- probability sampling method with a purposive sampling technique through a questionnaire distributed via Google Form. The results of the study showed that key opinion leaders had a positive and significant effect on consumer purchasing intention. In addition, brand awareness also had a positive and significant effect on purchasing intention. This study also proves that brand awareness can mediate the influence of key opinion leaders on purchasing intention, so that the higher consumer awareness of the Mustika Ratu brand, the stronger the influence of KOL on purchasing intention of the product. The implications of this study indicate that companies can maximize the use of KOL in Mustika Ratu's marketing strategy, especially on social media platforms such as TikTok. In addition, increasing brand awareness is an important key in strengthening the effectiveness of KOL on consumer purchasing intention.